Annual Review of the Sociology of Religion. Volume 15 (2024) : Change and Its Discontents. Religious Organizations and Religious Life in Central and Eastern Europe - Breskaya, Olga; Zrinščak, Siniša (Annual Review of the Sociology of Religion, 2025)
This volume presents a comparative study on the pivotal role of religion in social transformation of Central and Eastern Europe (CEE) over the past three decades. Organized into four thematic sections, it examines divergent patterns of religiosity and non-religious worldviews, secularization, religious presence in public life, and processes of identity formation. Comparison across the countries in the CEE reveals the absence of uniform and synchronic dynamics in the region. The geopolitical and cultural heterogeneity, the need to understand post-1989 social processes in the context of a much longer historical development of the region, and the importance of incorporating religious factors - are central to all contributions in this volume. Contributors are: Mikhail Antonov, Olga Breskaya, Zsuzsanna Demeter-Karászi, Jan Kaňák, Alar Kilp, Zsófia Kocsis, Tobias Koellner, Valéria Markos, András Máté-Tóth, Jerry G. Pankhurst, Gabriella Pusztai, Ringo Ringvee, Ariane Sadjed, Marjan Smrke, Miroslav Tížik, David Václavík, Jan Váně, Marko Veković, and Siniša Zrinščak.